Reviewers as Readers with Power: What a Case of Retranslation Says about Author, Translator and Reader Dynamics - Eker Roditakis, Arzu (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2017)
The Black Book, Orhan Pamuk’s second novel in English translation, was published in Güneli Gün’s translation in 1994 and in a retranslation by Maureen Freely in 2006. The decision for retranslation was mainly taken by the author on the basis of the criticism the first translation received from the reviewers, the most significant readers of translations with their power to consecrate foreign authors and their work in their new cultural settings. This study will present an analysis of the two translations of The Black Book, taking as its point of departure the criticism expressed in the reviews. The analysis will reveal the ways in which the first translation served as a criterion for the retranslation and how the two translators represented the author and his work differently, which was mainly enabled because of the changing status of Orhan Pamuk as an author in the English-speaking world between 1994 and 2006.